Splitting the P-Wave: Improved Evaluation of Left Atrial Substrate Modification after Pulmonary Vein Isolation of Paroxysmal Atrial Fibrillation - Aikaterini Vraka; Vicente Bertomeu-González; Fernando Hornero; Aurelio Quesada; Raúl Alcaraz; José J. Rieta (Sensors, 2021)
Atrial substrate modification after pulmonary vein isolation (PVI) of paroxysmal atrial fibrillation (pAF) can be assessed non-invasively by analyzing P-wave duration in the electrocardiogram (ECG). However, whether right (RA) and left atrium (LA) contribute equally to this phenomenon remains unknown. The present study splits fundamental P-wave features to investigate the different RA and LA contributions to P-wave duration. Recordings of 29 pAF patients undergoing first-ever PVI were acquired before and after PVI. P-wave features were calculated: P-wave duration (<semantics>PWD</semantics>), duration of the first (<semantics>PWDon<mtext>-</mtext>peak</semantics>) and second (<semantics>PWDpeak<mtext>-</mtext>off</semantics>) P-wave halves, estimating RA and LA conduction, respectively. P-wave onset (<semantics>PWon<mtext>-</mtext>R</semantics>) or offset (<semantics>PWoff<mtext>-</mtext>R</semantics>) to R-peak interval, measuring combined atrial/atrioventricular and single atrioventricular conduction, respectively. Heart-rate fluctuation was corrected by scaling. Pre- and post-PVI results were compared with Mann–Whitney U-test. <semantics>PWD</semantics> was correlated with the remaining features. Only <semantics>PWD</semantics> (non-scaling: <semantics>Δ=−9.84%</semantics>, <semantics>p=0.0085</semantics>, scaling: <semantics>Δ=−17.96%</semantics>, <semantics>p=0.0442</semantics>) and <semantics>PWDpeak<mtext>-</mtext>off</semantics> (non-scaling: <semantics>Δ=−22.03%</semantics>, <semantics>p=0.0250</semantics>, scaling: <semantics>Δ=−27.77%</semantics>, <semantics>p=0.0268</semantics>) were decreased. Correlation of all features with <semantics>PWD</semantics> was significant before/after PVI (<semantics>p<0.0001</semantics>), showing the highest value between <semantics>PWD</semantics> and <semantics>PWon<mtext>-</mtext>R</semantics> (<semantics>ρmax=0.855</semantics>). <semantics>PWD</semantics> correlated more with <semantics>PWDon<mtext>-</mtext>peak</semantics> (<semantics>ρ=</semantics> 0.540–0.805) than <semantics>PWDpeak<mtext>-</mtext>off</semantics> (<semantics>ρ=</semantics> 0.419–0.710). <semantics>PWD</semantics> shortening after PVI of pAF stems mainly from the second half of the P-wave. Therefore, noninvasive estimation of LA conduction time is critical for the study of atrial substrate modification after PVI and should be addressed by splitting the P-wave in order to achieve improved estimations.